Reinventing Native Advertising: The Impact of Short Video Campaigns in China's Digital Landscape - Zhimin, Zhong; Nasir, Junita Shariza Mohd; Siran, Zainudin Bin (Journal of Ecohumanism, 2025)
With the rapid development of digital technology, short video advertising in China's digital environment has shown unprecedented innovation in the field of native advertising. Especially on short video social platforms represented by TikTok, the rise of native short video ads has provided advertisers with unprecedented opportunities to develop tailored advertising campaigns to improve advertising effectiveness.This study takes TikTok short video advertising as an example to explore how short video native advertising reshapes the new form of native advertising. By comparing TikTok short video native advertising with traditional native advertising on Weibo and WeChat, the innovative performance of short video native advertising is explored. The analysis reveals that TikTok short video native advertising, with its user-centric approach, algorithmic capabilities and emphasis on authenticity, is taking its advertising ecosystem to new heights. By understanding the dynamics of short-form advertising on the TikTok platform, brands can strategically leverage this advertising format to engage with Chinese consumers in a more impactful way. This study contributes to a deeper understanding of the evolving nature of native advertising in the era of short-form content and highlights the importance of platforms like TikTok in shaping the future of digital marketing in China and around the world.